Solid state physics - Hunklinger, Siegfried; Enss, Christian (De Gruyter, 2022)
This highly regarded textbook provides a general introduction to solid state physics. It covers a wide range of physical phenomena occurring in solids and discusses fundamental concepts for describing them. Traditional themes are complimented by modern topics, like low dimensional systems, strongly correlated materials, nanoscale systems and non-crystalline solids, which are gaining increasing technical and scientific importance. Helpful for exam preparation are numerous exercises in all chapters
Aus dem Vorwort: This first English edition is a revised and supplemented version of the German textbook
Keywords: Lehrbuch; Festkörperphysik